Abordando la violencia de género durante el embarazo desde los servicios de salud materna: Proyecto Response - Eva Carmona-Del Río (Universitat de Barcelona, 2019)
The aim of the project «Multi-Agency Response for Reporting on Gender-Based Violence in Maternal Health Services» is to improve the capacity to detect and refer cases of gender-based violence during pregnancy in the maternal health services of the participating countries: Romania, Spain, France, Germany and Austria. Materials and Method To fulfill this purpose, interviews, legislative analysis at both national and international level, training of health professionals, collection of data, comparative analysis and dissemination of results have been carried out. Results It has been observed that pregnancy is a particularly vulnerable stage in a woman's life in which gender-based violence sometimes starts or worsens. Due to the characteristics of follow-up appointments, maternal health services are considered a particularly useful resource for early detection. Despite this circumstance, the lack of training in gender-based violence of health workers reduces the chances of detection and referral of cases. Conclusions The RESPONSE project has tried to respond to the lack of information and training of health and social-sanitary workers by developing key tools for the detection of symptoms and signs of violence, strengthening the collaboration of teams within and outside the health field and reinforcing the capacities of the participants when it comes to asking their patients about gender based violence and responding adequately to their demands.